Art Gallery Visitors’ Motivations - Jurėnienė, Virginija; Peseckienė, Dovilė (Information & Media, 2020)
The article discusses the motivational factors of visual art institution consumers. Analysis includes Falk’s identity-related theory of motivation for visiting art institutions that discusses how visitors’ experience begins before visiting a museum and is focused on the consumer’s attitude (identity) validation. Consumers’ motivation to visit an art institution depends on not only the proposals provided by the institution and their value to the consumer, but also on accessibility, the environment, and the personnel’s communication. The article introduces the motivations, expectations of consumers of the services provided by Kaunas Picture Gallery as well as evaluation of the services and infrastructure provided by the organisation obtained during study Visitors’ Expectations in Visual Art Institutions.
Keywords: Art gallery; visitor; motivational factors; J. Falk; accessibility and infrastructure; Kaunas Picture Gallery